2008
DOI: 10.1186/1471-2407-8-316
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise inhibits intestinal tumorigenesis in Apc Min/+mice and azoxymethane/dextran sulfate sodium-treated mice

Abstract: BackgroundEpidemiological studies suggest that physical activity reduces the risk of colon cancer in humans. Results from animal studies, however, are inconclusive. The present study investigated the effects of voluntary exercise on intestinal tumor formation in two different animal models, ApcMin/+ mice and azoxymethane (AOM)/dextran sulfate sodium (DSS)-treated mice.MethodsIn Experiments 1 and 2, five-week old female ApcMin/+ mice were either housed in regular cages or cages equipped with a running wheel for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 20 publications
3
43
1
2
Order By: Relevance
“…In experimental studies, a treadmill running exercise reduced the number of 1,2-dimethylhydrazine-induced aberrant crypt foci, a biomarker for colorectal carcinogenesis, in rats (14). In Apc min mice, voluntary (20) and treadmill (4) running exercise inhibited intestinal tumorigenesis. However, there is no information on BA metabolism in these studies showing inhibitory effects of exercise on the incidence of colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…In experimental studies, a treadmill running exercise reduced the number of 1,2-dimethylhydrazine-induced aberrant crypt foci, a biomarker for colorectal carcinogenesis, in rats (14). In Apc min mice, voluntary (20) and treadmill (4) running exercise inhibited intestinal tumorigenesis. However, there is no information on BA metabolism in these studies showing inhibitory effects of exercise on the incidence of colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…β-Catenin phosphorylation was elevated 3.3-fold in polyps from these exercised mice. Ju et al (262) found that colon tumorigenesis was ~40% greater in sedentary than voluntary running mice Apc Min/+ mice. The sedentary mice had higher IGF-1/IGFBP-3 ratios and aberrant β-catenin signaling, as compared to the voluntarily running mice (262).…”
Section: Colon Cancermentioning
confidence: 99%
“…Its effect on quality of life, fatigue, and CRC-specific mortality are not clear. In animal models of colon cancer, exercise has been demonstrated to significantly reduce colon cancer incidence [71,72].…”
Section: Exercisementioning
confidence: 99%